Effect of intranasal administration of NeuroEPO in the histological structure of the olfactory mucosa of Wistar rats - Ketty Suárez Borrás; Gisselle Fernández Peña; Giselle Puldón Seguí; Yamila Rodríguez Cruz; Carlos L. Pérez Hernández (Revista Habanera de Ciencias Médicas)
Introduction: Strokes and neurodegenerative diseases are major global health problems, not only because they cause high mortality and disability, but due to the lack of effective therapies. NeuroEPO, a variant of recombinant human erythropoietin (rHu-EPO) with a low sialic acid content, has shown encouraging results as a potential neuroprotective agent when administered intranasally. Objective: To determine the effect of intranasal administration of NeuroEPO on the histological structure of the olfactory mucosa of Wistar rats. Materials and Methods: An experimental, prospective, and longitudinal study was conducted on Wistar rats.  Ten healthy animals were randomly distributed into two groups of five each.  The control group received a vehicle (0.3 μl/g/day) and the treated group received NeuroEPO (300 μg/kg/day). Both treatments were administered intranasally for 28 days.  The histological characteristics of the olfactory mucosa were evaluated. The medians between the study groups were compared using the Mann-Whitney U test. Results: There were no alterations in the histological characteristics of the olfactory epithelium. However, slight hypertrophy and hyperplasia of the Bowman's glands were observed at the level of the lamina propria in the group treated with NeuroEPO. Conclusions: The administration of the nasal formulation of NeuroEPO did not induce histological alterations of the olfactory mucosa of Wistar rats under the experimental conditions of this research.